Strengthening the Institutional System for Management Confiscated Items on Evidence of The Object of Collateral in Corruption in Indonesia - La Uli; Agus Surono; Adek Junjunan Syaid (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
This research discusses the strengthening of the institutional system for managing confiscated evidence in corruption cases in Indonesia. The study employs a normative legal research method with a qualitative approach, focusing on a literature review of relevant regulations, legal principles, and theories. The research also uses an approach to laws and regulations and case studies to analyze issues related to the mismanagement of confiscated evidence. The findings suggest that the management of confiscated evidence should be entrusted to the RUPBASAN institution, which would be responsible for storing, maintaining, and securing the evidence to preserve its value and quality. RUPBASAN should not have any other interests besides evidence management. This study proposes granting RUPBASAN full authority over confiscated evidence, supported by legal frameworks and supervised by the President, to avoid overlapping authority with other institutions such as the police, the prosecutor's office, and the KPK. Furthermore, the Criminal Procedure Code, Article 44 (1), and Government Regulation No. 27 of 1983 outline the RUPBASAN's role in storing confiscated evidence. This concept also includes the sale of evidence that has permanent legal force, with proceeds directed into state revenue through Non-Tax State Revenue (PNBP). This approach aims to avoid misuse, damage, and accumulation of confiscated evidence at RUPBASAN, while providing economic benefits through interest on the funds from evidence sales deposited in banks. Ultimately, the concept seeks to enhance the management of confiscated evidence, ensuring justice and legal certainty for all parties involved.